Rabop sūnklāng khō̜mūn sinkhā nưng tambon nưng phalittaphan Čhangwat Nakhō̜n Sawan bon rabop khrư̄akhāi ʻinthœ̄net (Khana Witthayāsāt læ Thēknōlōyī, Mahāwitthayālai Rātchaphat Nakhō̜n Sawan, 2007)
The development on central system of 'one tambon one product' of Nakhon Sawan Province on the internet, upper Central Thailand.